The Evolution of the Abolition of the Death Penalty by International Human Rights Law in the United Nations - Lu Liang (Journal of Theory and Practice in Humanities and Social Sciences, 2023)
The death penalty, as the oldest and most severe punishment method, originated in the later period of primitive society with the emergence of the state, it can be seen as a tool for maintenance of society. Looking back at the history of human punishment, the first thought should be the death penalty because of obvious characteristics, such as irrevers-ibility. The kind of features can help researchers find the nature of the death penalty, not only can explore the value and meaning of the existence of the death penalty, also can find the necessity of abolishing the death penalty. The death penalty was rarely criticized in the 17th century, however, with the progress of human society and the development of social civilization, international community began to recognize the cruelty character of the death penalty in the eighteenth century. In 1764, the Italian criminal law scholar Beccaria advocated the abolition or limit the application of the death penalty for the first time, this idea used the social contract theory as the theoretical pillar and started from the bour-geois humanitarian standpoint. Therefore, the discussion of the death penalty was launched, and some countries began to abolishing the death penalty in the practice of criminal legislation. The death penalty as an ancient criminal law which has existed for a long time, it is disputed in the United Nations because of the deprivation of the right to life and the destruction of human rights, and the discussion of abolishing the death penalty have never stopped in the United Nations.